Physiotherapy management in genu ostheoartritis cases to increase functional capacity using ultrasound and isometric exercise modality at Rs. Idaman Banjarbaru - Samuel Arya Wahyudi; Arfian Hamzah; Muhammad Yusrin Al Gifari (UPPM Politeknik Unggulan Kalimantan, 2024)
Ostheoarthritis is a joint disorder characterized by progressive degeneration of joint cartilage resulting in narrowing of joint gaps including cartilage, subchondral, synovial fluid, and ligaments around the joint. Ultrasound is one of the non-pharmacological treatment methods that results in increased tissue temperature, increased blood flow as well as pain threshold and reduced spasm in muscles. Isometrric Exercise exercise therapy that serves to increase capacity respondents at Idaman Banjarbaru Hospital, using ultrasound modalities and isometric exercise. This research method is quantitative with a case study descriptive research design. The results of this study showed an increase in the interpretation of medium-weight to medium-light with an initial average of 56.7 which was included in the weight category to 34.4 With the mild final category, which concludes with this study, there has been an increase in functional capacity with the use of ultrasound modalities and isometric exercise in respondents who have bilateral genetic osteoarthritis.